De bar em bar sem perder os sentidos: (re)formulando estratégias à luz da estética organizacional - Santos, Kathyana Vanessa Diniz (2022)
Several actors, with varied experiences and judgments, participate in the strategic action of an organization and can influence the business strategic direction. In fact, the aesthetic involvement (physical, sensory and personal engagement with the world and its artifacts) of different individuals crucially affects organizational practices. Managers and researchers, however, have neglected this contributory potential of different agents and aesthetics to organizational life and performance. In order to remedy this situation, in this research I adopted the notion of Strategy as Practice and the sociomaterial approach of Organizational Aesthetics to understand how the sensory experiences and aesthetic judgments of different actors (like customers, frontline workers) present in Bars operations can help with the (re)formulation of business strategies. My intention was to explain how the aesthetic involvement of different actors (not commonly considered by Strategic Management) already influence the strategic action of organizations and discuss how this can be better used by management. Thus, I conclude the work by (1) proposing a perspective (Aesthetragizing) to think more broadly about the relationship between aesthetics, strategizing, (re)formulation of strategies and organizational performance; and (2) discussing a possible approach so that managers can incorporate this perspective of interweaving between aesthetics and strategy (Aesthetragizing) in their work contexts.